Respuesta :

Answer:

(11, 13)

Step-by-step explanation:

Carolyn's work is incorrect. Below is the correct solution:

Given:

[tex] 3x - 2y = 7 [/tex] ----› Equation 1

[tex] y = x + 2 [/tex] -----› Equation 2

Substitute y = (x + 2) in equation 1

[tex] 3x - 2y = 7 [/tex] ----› Equation 1

[tex] 3x - 2(x + 2) = 7 [/tex] (substitution)

[tex] 3x - 2(x) -2(+2) = 7 [/tex] (distributive property)

[Note: this is where Carolyn made a mistake]

[tex] 3x - 2x - 4 = 7 [/tex]

Collect like terms

[tex] x - 4 = 7 [/tex]

[tex] x = 7 + 4 [/tex] (addition property of equality).

[tex] x = 11 [/tex]

Substitute x = 11 in equation 2

[tex] y = x + 2 [/tex] -----› Equation 2

[tex] y = 11 + 2 [/tex] (substitution)

[tex] y = 13 [/tex]

✅The solution to the system of equations would be:

(11, 13)

ACCESS MORE